Association between Prenatal and Postnatal Psychological Distress and Toddler Cognitive Development: A Systematic Review. - Dawn Kingston; Sheila McDonald; Marie-Paule Austin; Suzanne Tough (PLoS ONE, 2015)
Purpose Maternal psychological distress is one of the most common perinatal complications, affecting up to 25% of pregnant and postpartum women. Research exploring the association between prenatal and postnatal distress and toddler cognitive development has not been systematically compiled. The objective of this systematic review was to determine the association between prenatal and postnatal psychological distress and toddler cognitive development. Methods Articles were included if: a) they were observational studies published in English; b) the exposure was prenatal or postnatal psychological distress; c) cognitive development was assessed from 13 to 36 months; d) the sample was recruited in developed countries; and e) exposed and unexposed women were included. A university-based librarian conducted a search of electronic databases (Embase, CINAHL, Eric, PsycInfo, Medline) (January, 1990-March, 2014). We searched gray literature, reference lists, and relevant journals. Two reviewers independently evaluated titles/abstracts for inclusion, and quality using the Scottish Intercollegiate Guideline Network appraisal tool for observational studies. One reviewer extracted data using a standardized form. Results Thirteen of 2448 studies were included. There is evidence of an association between prenatal and postnatal distress and cognitive development. While variable effect sizes were reported for postnatal associations, most studies reported medium effect sizes for the association between prenatal psychological distress and cognitive development. Too few studies were available to determine the influence of the timing of prenatal exposure on cognitive outcomes. Conclusion Findings support the need for early identification and treatment of perinatal mental health problems as a potential strategy for optimizing toddler cognitive development.